Comprehensive Analysis of Ferroptosis-Related LncRNAs in Breast Cancer Patients Reveals Prognostic Value and Relationship With Tumor Immune Microenvironment - Xu, Zhengjie; Jiang, Suxiao; Ma, Juan; Tang, Desheng; Yan, Changsheng; Fang, Kun (Frontiers in Surgery, 2021)
Background: Breast cancer (BC) is a heterogeneous malignant tumor, leading to second major causes of female mortality. The purpose of this study is to establish an in-depth relationship between ferroptosis-related LncRNA (FRlncRNA) and the prognosis as well as immune microenvironment of BC patients. Methods: We downloaded and integrated the gene expression data and the clinical information of BC patients from The Cancer Genome Atlas (TCGA) database. Co-expression network analysis and univariate Cox regression analysis were performed to screen out the FRlncRNAs related to prognosis. Cluster analysis was adopted to explore the difference of immune microenvironment between clusters. Furthermore, we determined the optimal survival-related FRLncRNAs for final signature by LASSO Cox regression analysis. Afterwards, we constructed and validated the prediction models, which were further tested in different subgroups. Results: A total of 31 FRLncRNAs were filtrated as prognostic biomarkers. Two clusters were determined, and C1 showed better prognosis and higher infiltration level of immune cell, such as B cells naive, Plasma cells, T cells CD8, and T cells CD4 memory activated. However, there were no significantly different clinical characters between clusters. Gene Set Enrichment Analysis (GSEA) revealed that some metabolism-related pathway and immune-associated pathway were exposed. What’s more, 12 FRLncRNAs were determined by LASSO analysis and used to construct a prognostic signature. In both training and testing sets, patients in high-risk group had a worse survival than low-risk patients. The AUCs of ROC curves were about 0.700, showing positive prognostic capacity. More notably, through comprehensive analysis of heatmap, we regarded LINC01871, LINC02384, LIPE-AS1 and HSD11B1-AS1 as protective LncRNAs, while LINC00393, AC121247.2, AC010655.2, LINC01419, PTPRD-AS1, AC099329.2, OTUD6B-AS1 and LINC02266 were classified as risk LncRNAs. At the same time, patients in the low-risk groups were more likely to be assigned to C1 and had a higher immune score, which were consistent with a better prognosis. Conclusion: Our research indicated that ferroptosis-related prognostic signature could be used as novel biomarkers for predicting the prognosis of BC. The differences in the immune microenvironment exhibited by BC patients with different risks and clusters suggested that there may be a complementary synergistic effect between ferroptosis and immunotherapy.